Partisipasi Masyarakat dalam Program Gerakan Tanam dan Pelihara 50 Juta Pohon terhadap Tingkat Penjualan Bibit Tanaman Hutan di Provinsi Jawa Barat (Suatu Kasus pada Pengada/Pengedar Bibit Tanaman Hutan di Provinsi Jawa Barat) - Finauly Hadiyantini; Dety Sukmawati; Tuti Gantini (Paspalum: Jurnal Ilmiah Pertanian, 2022)
This study aims to determine how the implementation of The Movement of 50 Million Trees Planting and Caring (GTPP) program in terms of the volume of sales of seeds to forest plant seed suppliers/distributors, types of seeds, area and percentage of each community participation group; the effect of the GTPP program on the level of seed sales to forest plant seed suppliers/distributors in West Java; as well as the variable of community participation which has the most influence on the level of seed sales to forest plant seed suppliers/distributors in West Java Province. The results showed that community participation in the implementation of the GTPP program based on data for the period 2020 to 2021 seen from the type of seed the most were Sengon seedlings as many as 5,233,197 stems, with the most sales by CV. Putra Dilan Jaya as many as 2,013,768 stems and based on the largest area is from Sukabumi Regency as many as 3,485,988 stems. Based on the results of statistical tests for the average difference of the variables of community participation in the GTPP program, namely participating in providing seeds for marriage, birthday, making STNK/PKB for R2 vehicles, making STNK/PKB for R4 vehicles, Graduation, promotion, ASN and Business Entities obtaining permits (IMB/Business Permits and others) there is a significant average difference. The variable of community participation that has the most influence on the sale of tree seedlings is the Business Entity that obtains a permit (IMB/Business Permit and others), with the highest average sales of 4205 or 55.43% of tree seedlings and has a significant average difference. with other variables.